Frontispiece: Towards Sustainable C−H Functionalization Reactions: The Emerging Role of Bio‐Based Reaction Media. Issue 51 (12th September 2018) - Santoro, Stefano; Marrocchi, Assunta; Lanari, Daniela; Ackermann, Lutz; Vaccaro, Luigi
Abstract : Transition‐metal catalyzed C−H functionalization reactions have progressed enormously, becoming a useful tool in organic synthesis and a practical alternative to well‐established methodologies. Very recently, research efforts have also been devoted to developing more sustainable C−H functionalization protocols, in order to increase their applicability. One of the most promising approaches in this sense is represented by the substitution of common reaction media with bio‐based solvents. In the Concept by S. Santoro, L. Vaccaro et al. onpage 13383 ff., a general perspective on the benefits of this approach is given, followed by key literature examples.